Paleta 5 a handbook for visual artists. - Philippines. National Commission for Culture and the Arts. (Manila National Commission for Culture and the Arts, 2002)
Provides a listing of places, events and institutions concerned with Philippine arts. The work is aimed to help Filipino artists expose their craft to a wider audience and meet others who share their passion. This issue contains sections written in Filipino and an additional "printmaking" section.
"A project of the NCCA Committee on Visual Arts".
Keywords: Art, Philippine -- Handbooks, manuals, etc